ijps 2021
DOI: 10.36468/pharmaceutical-sciences.809
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Immunomodulatory Potential of Aqueous Extract of Different parts of Terminalia catappa L.

Abstract: Venkatalakshmi et al.: Immunomodulatory Potential of Terminalia catappa LModulation of immunity is the most sought therapeutic effect as many human ailments arise because of imbalance in immune mechanisms. In the current corona virus disease scenarios also, the role of immunity to combat the dreadful virus has been well emphasized. Hence the present study aims at evaluating the immunomodulatory potential of aqueous extract obtained from the different parts such as bark, fruit and wood of Terminalia catappa. Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The evaluation of the qualitative chemical profile of the T. catappa extract used in this study has shown, among others, the presence of flavonoids such as quercetin, rutin, isoorientin, vitexin and isovitexin, as well as the presence of hydrolysable tannins such as gallic acid and ellagic acid, and also triterpenoid derivatives such as asian and ursolic acid (BOSCARATO et al, 2021;TERÇAS et al, 2017;VENKATALAKSHMI, P.;BRINDHA,2021;MININEL et al, 2014). These flavonoid and non-flavonoid polyphenols, abundant compounds derived from plant secondary metabolism, are related to the ability of medicinal plants to neutralize free radicals (MOHAMMED et al,2022), being attributed to them anti-inflammatory and antioxidant activities of T. catappa (YADAV et al, 2021;IHEAGWAM et al, 2022).…”
Section: Cliumorg | 260mentioning
confidence: 88%
“…The evaluation of the qualitative chemical profile of the T. catappa extract used in this study has shown, among others, the presence of flavonoids such as quercetin, rutin, isoorientin, vitexin and isovitexin, as well as the presence of hydrolysable tannins such as gallic acid and ellagic acid, and also triterpenoid derivatives such as asian and ursolic acid (BOSCARATO et al, 2021;TERÇAS et al, 2017;VENKATALAKSHMI, P.;BRINDHA,2021;MININEL et al, 2014). These flavonoid and non-flavonoid polyphenols, abundant compounds derived from plant secondary metabolism, are related to the ability of medicinal plants to neutralize free radicals (MOHAMMED et al,2022), being attributed to them anti-inflammatory and antioxidant activities of T. catappa (YADAV et al, 2021;IHEAGWAM et al, 2022).…”
Section: Cliumorg | 260mentioning
confidence: 88%
“…Stimulating immune responses is desirable for patients with a compromised immune system, including patients with HIV and AIDs. Alternatively, immunosuppression alleviates aggressive pathological immune responses, including the rejection of transplanted organs, inflammatory diseases, and autoimmune disorders, among others [ 19 ]. Pyrogallol is a commercially available polyphenol [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Te most recent achievement in this feld is the approval of an immunomodulator, colchicine, an alkaloid isolated from Colchicum autumnale, by the Federal Drug Administration in 2009 for treating acute gout fares and Familial Mediterranean fever [16]. Several Terminalia species, including T. arjuna, T. bellirica, T. catappa, and T. chebula, modulate immune responses [17][18][19][20][21][22][23][24][25][26][27]. Te modulation of the immune system encompasses any adjustment of immune responses, including inhibition or stimulation of its function [28].…”
Section: Introductionmentioning
confidence: 99%
“…Previous phytochemical studies conducted on the extracts of T. catappa leaves have shown that the species possesses mainly compounds of the phenolic classes [ 11 , 26 , 27 ], including flavonoids [ 26 , 27 , 28 ] and hydrolyzable tannins [ 11 , 27 ]. Diverse classes of metabolites found in T. catappa , which are known for their benefits to human health, may also play important ecological roles.…”
Section: Introductionmentioning
confidence: 99%